The table represents a greater unit rate of change.
<span>To answer this question, you need to multiply the number inside the bracket first. Then you can move the number to the right side of the equal sign and keep the x on the left side of the equal sign. The step would be like this
2(x – 5) - 6x= -22
(2x - 10) - 6x = -22
2x - 6x = -22 +10
-4x= -12
x= -12/-4
x=3</span>
Answer:
hmmmmm
Step-by-step explanation:
Answer:
Step-by-step explanation:
<u>Exponential function is:</u>
<u>If we consider the time difference in years as x and the initial population as a, then we get:</u>
<u>Find the value of b:</u>
- b¹⁰ = 675647/617594
- b¹⁰ = 1.09399864636
- b = 1.09399864636^(1/10)
- b = 1.009 (rounded)
<u>The equation we got is:</u>
Here we have y- population after x years since 2010, x - the number of years since 2010 and 1.009 is the population growth rate.